Interoperabilidade entre dispositivos como serviços: uma abordagem interdisciplinar - Claro, Daniela Barreiro; Jesus, Luis Emanuel Neves de; Gomes, Alexandre Silva; Figueiredo, Roberto de Cerqueira; Correia, Mariane Dourado; Sena, Cleiton Fernando Lima; Glauber, Rafael; Azevedo, Wellington Assunção; Alfonzo, José Alejandro Moreno; Santana, Luan Silva; Jadidi, Aydin (Anais do Workshop de Informática na Escola (WIE), 2016)
Heterogeneous devices in IoT need to communicate and web services can provide such interoperability. However, it is necessary to embed those web services on such devices. Our work describes the development of the course MAT700 at the Federal University of Bahia aimed to provide knowledge to interoperate heterogeneous devices by web services. Finally, we evaluated various aspects related to the course, including learning, content, didactics, in order to validate our proposed interdisciplinary methodology. The results showed that the interdisciplinary contributed to the individual learning and growth learners.